Detecção de fluorescência por imagens digitais em placas de spot tests fabricadas por tecnologia de impressão 3D - SILVA, Emelle Kelly Nascimento da (2019)
A fluorescent method based on digital images and spot test was developed to determine quinine in beverages. Thus, a smartphone as a detector and a microplate produced in a 3D printer to accommodate the standard solutions and samples were used. To acquire the fluorescent images, a chamber made of recyclable paper with four ultra-brightness ultraviolet light emission diode (UV-LED) with maximum wavelength at 360 nm was developed. The blue channel (B) presented greater sensitivity and precision compared to other channels and used mathematical models. The linear analytical curve ranged of 0.50 to 4.50 mg L-1 with a correlation coefficient of 0.998. The limits of detection and quantification were 0.04 and 0.12 mg L-1, respectively. The precision and the accuracy were evaluated and a relative standard deviation ranged of 0.93% to 1.84% and a relative error lower than 2% were obtained. Moreover the results supplied by the proposed device were compared to a conventional spectrofluorimeter by employing the paired t test and the experimental t test ranged of 0.13 to 0.91, which are less than the tabulated value of 2.57 at the 95% confidence level for (n = 6). Additionally, the recovery values ranged of 94.0% to 110% and the analytical frequency was 10 analyzes per minute. Supported by the results, the proposed method demonstrated to be fast, accuracy, precise, and less aggressive to the environmental due to the generated low waste and the use of biodegradable microplates, when it is compared to a conventional spectrofluorimeter.